ANALISIS FAKTOR PENGARUH KETEPATAN WAKTU PELAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR DI BEI (Students' Journal of Accounting and Banking, 2012)
This research refers to research conducted by Natallia Anggraenie (2006). Any limitations of previous studies, the researcher interested in conducting a test of the factors that affect the timeliness of financial reporting. The study aims to determine whether the debt to equity, profitability and liquidity affect the timeliness of corporate financial reporting.Study sample with the criteria specified sample obtained (n) of 57 manufacturing companies that go public on the Stock Exchange Indonesia for 4 years so the amount of data 56 x 4 = 224 observation data. Data analysis tool used is logistic regression.The results of data processing can be concluded that the debt to equity ratio does not significantly influence the timeliness of financial reporting; profitability (ROI) does not significantly influence the accuracy of the publication of financial statements and liquidity significantly influence the timeliness of financial reporting.Keywords: debt to equity ratio, profitability, liquidity and the timeliness of corporate financial reporting